1984
DOI: 10.3168/jds.s0022-0302(84)81374-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants of Casein and Milk Serum Proteins with Milk, Fat, and Protein Production by Dairy Cattle

Abstract: Polyacrylamide gel electrophoresis methods were used to phenotype caseins for 2045 cows and milk serum proteins for 3870 cows distributed in 63 Quebec dairy herds. Frequencies were: alpha s1-casein A .003, alpha s1-casein B .970, alpha s1-casein C .027; beta-casein A1 .561, beta-casein A2 .421, beta-casein A3 .011, beta-casein B .007; kappa-casein A .744, kappa-casein B .256; beta-lactoglobulin A .387, beta-lactoglobulin B .613; alpha-lactalbumin B 1.00. Overall unadjusted means for 305-day production in first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
1
8

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 7 publications
11
67
1
8
Order By: Relevance
“…The results of this study are consistent with those reported by [6,7], who concluded that the BB genotype for κ-Cs determines the best milk properties for cheese production because of the greater firmness in the curd and smaller time required for the formation of small micelles. With regard to the homozygous AA genotype, these animals had lower casein contents and, as a consequence, a higher proportion of large micelles, which reduces the curd yield efficiency.…”
Section: Kappa -Casein (Csn3) Genotypessupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study are consistent with those reported by [6,7], who concluded that the BB genotype for κ-Cs determines the best milk properties for cheese production because of the greater firmness in the curd and smaller time required for the formation of small micelles. With regard to the homozygous AA genotype, these animals had lower casein contents and, as a consequence, a higher proportion of large micelles, which reduces the curd yield efficiency.…”
Section: Kappa -Casein (Csn3) Genotypessupporting
confidence: 83%
“…These results do not agree with those obtained by Haenlein [58] and Graml [59] in relation to the stained brown bavárico and Guernsey, who claim that cows carrying the AB genotype reach a higher milk production compared to those with the homozygous genotype AA. On the contrary, [6,60,61] they reported the highly significant effect of genotype BB on this feature in the Holstein breed.…”
Section: Allelic Variants Of κ-Csmentioning
confidence: 99%
“…Aleandri et al (1990) relataram efeito quantitativo de variantes genotípicas do gene para β-lactoglobulina sobre a composição do leite e as propriedades do queijo. O alelo B, para β-lactoglobulina, está associado a alto teor de gordura e caseína em rebanhos leiteiros, enquanto o genótipo AA apresenta maiores teores de proteína de soro e proteína total (Ng-Kwai-Hang et al, 1984;Kumar et al, 2006). Apesar da importância da associação entre esses genes e o desempenho médio animal, representado pelas curvas de produção de leite, gordura, proteína e sólidos totais, ainda não há estudos que a utilizem na avaliação genética e fenotípica de indivíduos, em programas de seleção assistida por marcadores.…”
Section: Introductionunclassified
“…E.g., the CSN1S1 BB genotype correlated with higher milk production in some cases (Ng-Kwai-Hang et al, 1984;Aleandri et al, 1990;Sang et al, 1994) but there was also an evidence for the superiority of the hetrozygous BC genotype (Micinski et al, 2007). Our results support the positive effect of the BC genotype on the milk yield being about 9.5% higher than the homozygous genotypes.…”
Section: Application Of Milk Proteins Genetic Polymorphism or Selectimentioning
confidence: 99%